Parallel fabrication of macroporous scaffolds. Issue 7 (31st March 2018) - Dobos, Andrew; Grandhi, Taraka Sai Pavan; Godeshala, Sudhakar; Meldrum, Deirdre R.; Rege, Kaushal
Abstract: Scaffolds generated from naturally occurring and synthetic polymers have been investigated in several applications because of their biocompatibility and tunable chemo‐mechanical properties. Existing methods for generation of 3D polymeric scaffolds typically cannot be parallelized, suffer from low throughputs, and do not allow for quick and easy removal of the fragile structures that are formed. Current molds used in hydrogel and scaffold fabrication using solvent casting and porogen leaching are often single‐use and do not facilitate 3D scaffold formation in parallel. Here, we describe a simple device and related approaches for the parallel fabrication of macroporous scaffolds. This approach was employed for the generation of macroporous and non‐macroporous materials in parallel, in higher throughput and allowed for easy retrieval of these 3D scaffolds once formed. In addition, macroporous scaffolds with interconnected as well as non‐interconnected pores were generated, and the versatility of this approach was employed for the generation of 3D scaffolds from diverse materials including an aminoglycoside‐derived cationic hydrogel ("Amikagel"), poly(lactic‐co‐glycolic acid) or PLGA, and collagen. Macroporous scaffolds generated using the device were investigated for plasmid DNA binding and cell loading, indicating the use of this approach for developing materials for different applications in biotechnology. Our results demonstrate that the device‐based approach is a simple technology for generating scaffolds in parallel, which can enhance the toolbox of current fabrication techniques. Abstract : A reusable and cost‐effective device is described, which utilizes in‐situ porogen fusion, in‐situ polymerization and gelation to facilitate synthesis and easy recovery of polymer scaffolds in high‐throughout. The device was employed for the generation of multiple scaffold types, including an aminoglycoside‐derived cationic hydrogel (Amikagel), collagen and poly(lactic‐co‐glycolic acid) or PLGA and was shown to generate scaffolds with differing morphologies (macroporous and non‐porous). Macroporous scaffolds generated using the device were investigated for plasmid DNA binding and cell loading.